What Predicts Financial (In)Stability? A Bayesian Approach - Michael Sigmund; Ingrid Stein (Credit and Capital Markets – Kredit und Kapital, 2017)
This paper contributes to the literature on early warning indicators by applying a Bayesian model averaging approach. Our analysis, based on Austrian data, is carried out in two steps: First, we construct a quarterly financial stress index (AFSI) quantifying the level of stress in the Austrian financial system. Second, we examine the predictive power of various indicators, as measured by their ability to forecast the AFSI. Our approach allows us to investigate a large number of indicators. The results show that banks' share price growth and cross-border lending are among the best early warning indicators. – – Wie lässt sich Finanzmarktstabilität prognostizieren? Ein Bayesianischer Ansatz In dieser Arbeit wird ein bayesianischer Ansatz zur Bestimmung von Frühwarnindikatoren für Finanzkrisen beschrieben. Unsere Analyse basiert auf österreichischen Daten und teilt sich in zwei Schritte auf: Im ersten Schritt entwickeln wir einen vierteljährlichen Index zur Messung des Stresses im österreichischen Finanzsystem (Austrian Financial Stress Index, AFSI). Im zweiten Schritt überprüfen wir die Vorhersagekraft verschiedener Indikatoren für den AFSI. Unser Ansatz erlaubt die Überprüfung einer gro???en Anzahl an Indikatoren. Die Ergebnisse zeigen, dass die Renditen von Bankaktien und grenzüberschreitende Kredite die besten Frühwarnindikatoren sind.
Keywords: G01; G28; 330; Early warning indicators; financial crisis; financial stress index; Bayesian model averaging